2015
DOI: 10.1016/j.aim.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Nonvanishing of Koecher–Maass series attached to Siegel cusp forms

Abstract: We prove a nonvanishing result for Koecher-Maass series attached to Siegel cusp forms of weight k and degree n in certain strips on the complex plane. When n = 2, we prove such a result for forms orthogonal to the space of the SaitoKurokawa lifts 'up to finitely many exceptions', in bounded regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…So, for a fixed 𝑚 ⩾ 1 and 𝛼 very close to 𝜋∕2, we have < 1 2 𝐹(𝑇), we arrive at a contradiction and it completes the proof of the theorem.…”
Section: Proof Of the Theoremmentioning
confidence: 54%
See 1 more Smart Citation
“…So, for a fixed 𝑚 ⩾ 1 and 𝛼 very close to 𝜋∕2, we have < 1 2 𝐹(𝑇), we arrive at a contradiction and it completes the proof of the theorem.…”
Section: Proof Of the Theoremmentioning
confidence: 54%
“…Koecher–Maass series attached to Siegel modular forms and its properties have been well studied [6]. This series has been studied to establish several other results, such as converse theorem for Siegel modular forms, non‐vanishing of Koecher–Maass series inside a strip [1] and many others. It is not known that Koecher–Maass series are genuine L$L$‐functions nor if they are expected to satisfy the Riemann hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, Kohnen ( [7]) showed that for k sufficiently large there exists a Hecke eigenform f of weight k such that L * (f, s) = 0 at any point on the line segments Im(s) = t 0 , k−1 2 < Re(s) < k 2 − ǫ, k 2 + ǫ < Re(s) < k+1 2 , for any given real number t 0 and a positive real number ǫ. This result and its method inspired various works on non-vanishing of L-values for different kinds of modular forms (see [2,5,8]). This paper concerns the non-vanishing of the product L * (f, s)L * (f, w) (s, w ∈ C) on average.…”
Section: Introductionmentioning
confidence: 75%
“…2010 Mathematics Subject Classification Primary 11F37, Secondary 11F66 Finally, addressing the reader interested in Siegel modular forms, we would like to mention the papers [3,5] where corresponding non-vanishing results for Koecher-Maass series are given.…”
Section: Introductionmentioning
confidence: 99%